CHILD MARRIAGE IN SHORT STORIES FROM INDONESIA AND BANGLADESH: VICTOR, SURVIVOR, AND VICTIM - Novita Dewi (Sanata Dharma University, 2018)
Early marriage is a total destruction to the human rights of children. Contrary to the conviction that child marriage in rural, developing countries is inextricably linked with their cultural backwardness, violence against women need to be examined and addressed in terms of the specific socio-economic and cultural conditions as to why girls, adolescents and young women are forced to live and marry in their young age. This article examines two shorts stories from Indonesia to be analyzed comparatively with another story from Bangladesh to show the limit of mainstream feminist perspectives that often put the blame on minority cultures. The present study reveals that first, child marriages in both countries are largely driven by such factors as poverty, economic dependency, lack of education, and dowry in Bangladeshs case. Secondly, the ways in which authors depict child marriages vary, i.e. it is either perpetuating the violence in child marriage, or critically depicting child marriage as an aberrant patriarchal practice. Taken together, the child brides play their respective role as victor, survivor, or victim.